148 Partial Lung Aeration Causes Ventilation/Perfusion Mismatch in the Lungs at Birth. (October 2012) - Hooper, SB; Lang, J; Pearson, JT; Wallace, MJ; Siew, ML; Kitchen, MJ; Fouras, A; Wheeler, K; Polglase, GJ; Pas, AB te
Abstract : Background: Although lung aeration increases pulmonary blood flow (PBF) at birth, the regional relationships between lung aeration and the increase PBF are unknown. We investigated the effect of partial ventilation on pulmonary vessels immediately after birth using simultaneous phase contrast X-ray imaging and angiography. Method: Newborn rabbits were delivered near-term (~30 d GA; term ~32 d GA) and an iodine contrast agent was infused into the jugular vein before and then during both unilateral (of the right lung) and then ventilation of both lungs. Visible vessels were counted and diameters and integrated intensity line profiles that transected vessels at different locations were measured; the latter provides a relative measure of PBF. Results: Unilateral ventilation of the right lung increased visible vessel number (from 15±1 to 44±4), vessel diameter (from 493±80µm to 543.2±84.3µm) and integrated intensity (from 2496±472 µm.AU to 6594±658 µm.AU) in the left lung while it was still liquid-filled and unaerated. As a result, the visible vessel number of perfused pulmonary vessels (right: 42±4, left: 44±4), mean vessel diameters and integrated intensity (left: 6594±658 µm.AU, right: 8012±1423 µm.AU) were not different between aerated and non-aerated lung regions. Angiography videos demonstrating the spatial and temporal changes in PBF after birth will also be presented. Conclusion: Partial lung aeration promotes a global increase in PBF resulting in a highly significant ventilation/perfusion mismatch in unventilated lung regions. These observations indicate that a previously unsuspected mechanism contributes to the increase in PBF at birth.